Early-life infectious disease exposure, the “hygiene hypothesis,” and lifespan: Evidence from hookworm disease - Ralph Lawton (Proceedings of the National Academy of Sciences, 2025)
Exposure to infectious disease in early life may have long-term ramifications for health and lifespan. However, reducing pathogen exposure may not be uniformly beneficial. The rise of modern sanitation and reduction of infectious diseases has been implicated in increasing levels of allergy and immune dysregulation: termed, the “hygiene hypothesis.” This study leverages quasi-experimental variation from combining precampaign hookworm exposure with the Rockefeller Sanitary Commission’s deworming campaign in the early 20th century to rigorously examine the impacts of childhood hookworm exposure on adult lifespan and morbidity. Findings show deworming before age five leads to 2.5 additional months of life in a large sample of adult death records. Further, decreasing hookworm exposure is related to improvements in biomarkers for inflammation and skin-tested allergies, in contrast to predictions of the “hygiene hypothesis.” Placebo tests using health outcomes that should not be affected by deworming do not show similar patterns. Overall, childhood deworming leads to improvements in morbidity and lifespan decades later.